Leveraging the Supply Chain Development to Achieve Greater Impact in the Industry - Korinna, Tetyana (World Bank, Washington, DC, 2012)
The International Finance Corporation (IFC) Vinnytsya Fruit Supply-Chain Development Project works to strengthen the farmer supply chain for one of the world's largest fruit processors. This smart lesson focuses on the project's experience using public education tools demonstration programs, site tours, publications, television, and DVDs for increasing the understanding and knowledge of industry stakeholders about market potential and development, for public discussion and promotion of needed regulatory improvements, and even for maintaining relations with donors.